Pengaruh Kinerja Tenaga Kependidikan Terhadap Kepuasan Mahasiswa melalui Mediasi Kualitas Pelayanan - Wibawa, I Wayan Sucipta; Usadi, Made Pradnyan Permana; Dwinata JS, I Putu Wahyu (Universitas Batanghari Jambi, 2024)
Higher education as one of the institutions engaged in education, must be able to provide maximum service in order to be able to increase student satisfaction in carrying out lectures properly. This research was conducted to determine the effect of academic division performance on student satisfaction through the mediation of service quality at Mahasaraswati University Denpasar. The data collection method used a questionnaire given to 100 student with purposive sampling technique. Data collection techniques using interviews, questionnaires and documentation. The data collection technique with Non-Probability Sampling uses the Accidental Sampling approach. Collecting data with a questionnaire that uses a Likert scale. This type of research uses quantitative research methods. Data analysis techniques used SEM (Structural Equation Modeling) with the PLS (Partial Least Square) approach, and the VAF test to test mediation. The results showed that academic division performance had a positive effect on student satisfaction, academic division performance had a positive effect on service quality, service quality had a positive effect on student satisfaction, and service quality was able to mediate the effect of academic division performance on student satisfaction. The findings in this study have implications that in order to increase student satisfaction, academic division at institutions are expected to be able to perform according to the standards set by the institution, where this will be able to improve the quality of service so that it causes a high level of satisfaction from students when they need information related to the lecture process.